Histamine enhances keratinocyte-mediated resolution of inflammation by promoting wound healing and response to infection. - Gutowska-Owsiak, D; Selvakumar, T; Salimi, M; Taylor, S; Ogg, G (2014)
BACKGROUND: The role of the epidermis in the immune response is well known. While multiple cytokines are implicated in keratinocyte-mediated infection clearance and wound healing, little is known about the involvement of keratinocytes in promoting resolution of inflammation. AIM: To assess effects of histamine stimulation on keratinocyte function. METHODS: We performed a combined microarray/Gene Ontology analysis of histamine-stimulated keratinocytes. Functional changes were tested by apoptosis assessment and scratch assays. Histamine receptor involvement was also assessed by blocking wound closure with specific antagonists. RESULTS: Histamine treatment had extensive effects on keratinocytes, including effects on proinflammatory responses and cellular functions promoting wound healing. At the functional level, there was reduced apoptosis and enhancement of wound healing in vitro. At the receptor level, we identified involvement of all keratinocyte-expressed histamine receptors (HRHs), with HRH1 blockage resulting in the most prominent effect. CONCLUSIONS: Histamine activates wound healing and infection clearance-related functions of keratinocytes. While enhancement of histamine-mediated wound healing is mediated predominantly via the HRH1 receptor, other keratinocyte-expressed receptors are also involved. These effects could promote resolution of skin inflammation caused by infection or superficial injury.